(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
This study aimed to identify the effect of feedback on the credibility of the source towards constructive feedback and self-efficacy of teaching. Specifically, the objective of this study was to determine whether the credibility of the source of feedback be the moderator of the relationship between the constructive feedback and self-efficacy of teaching. In this study, a total of 411 lecturers from three premier polytechnics and two polytechnics which achieved excellent recognition through polyrate took part. Data for this study were collected through a questionnaire which was adapted from previous researchers questionnaire. Finding shows that higher academic qualification does have an effect on feedback credibility. Hypothesis testing is done by using multiple regression analysis and hierarchical multiple regression analysis. Findings have shown the constructive feedback and credibility of feedback have an influence on self-efficacy of teaching. In addition, the findings also indicate the credibility of the feedback was moderator of the relationship between the constructive feedback and self-efficacy of teaching. In terms of implications, middle leaders in educational organizations should enhance the skills, knowledge, and credibility in giving constructive feedback to shape and improve self-efficacy among his followers.